The Moro woman a look into the sensemaking process of the Moro Women, Inc. - Reyes, Sergie C.
This reseach aims to study the communicative process of sensemaking of the Moro Women, Inc. by observing a focus group discussion among six members. The goal is to construct a collective concept about the Moro woman society by reducing equivocality, or ambiguity, about it. Equivocality was determined in the objectives of the organization and was affirmed in the individual interviews with participants of the discussion. The equivocality was about the Moro woman having problems with rights, responsibilities, participation in society, and religion. After which, the discussion took place where sensemaking, involving Enactment, Selection, and Retention, was at play to reduce equivocality. In Enactment, two themes were highlighted and were dominant during discussion, ?Discriminated? and ?Peacekeepers?' because they were given time to be talked about. In selection, members shared past experiences to explain the themes. They say they are discriminated in jobs, applications, history, education, law, government, and by non-Moro and media perceptions. Their role as peacekeepers was based from examples they gave on their involvement in the Maguindanao Massacre and their family/house role. In retention, ideas and actions retained by the organization were noted. They feel the need to ?always prove that they are good?, fight for ?equal opportunities?, ?treat non-Moro's well by living by example?, accept they are complimentary to men?, and to be ?united?. In addition, they also think that there is a ?constant struggle? of the Moro women and that they are ?supporters of peace?. In general, the Moro Woman has problems with rights, responsibilities, participation in society, and religion because she is discriminated and people have distorted views about her roles. The ideas in the Retention phase were able to explain the actions of the organization and their objectives